Real-space multiple-scattering theory of XMCD including spin-orbit interaction in scattering process. (May 2016) - Koide, Akihiro; Niki, Kaori; Sakai, Seiji; Fujikawa, Takashi
Abstract: The effects of the spin-orbit interaction on surrounding atoms for XMCD spectra are studied by a real-space multiple-scattering theory. The present numerical calculation for Fe K -edge XMCD spectra from BCC iron demonstrates the importance of the spin-orbit interaction on scattering atoms, which has been disregarded in previous works. These effects will be inevitable for K -edge XMCD analyses of light elements surrounded by heavy magnetic atoms.